ARCHITECTING AGILITY: TRANSFORMING HUMAN CAPITAL CAPABILITY INTO ORGANIZATIONAL RESILIENCE THROUGH TALENT MOBILITY FRAMEWORKS - Isma Budiawan; Mukhlis Mukhlis (Journal of Loomingulisus ja Innovatsioon, 2026)
Organizations increasingly operate in environments characterized by technological disruption, workforce transformation, and persistent uncertainty, making organizational resilience a strategic priority. Conventional human resource practices frequently emphasize talent acquisition and retention while giving insufficient attention to internal talent mobility as a mechanism for developing adaptive organizational capability. This study aimed to examine how talent mobility frameworks transform human capital capability into organizational resilience through organizational learning, workforce flexibility, leadership development, and digital workforce readiness. A mixed-methods sequential explanatory design was employed involving 2,850 employees from thirty-six organizations across multiple industries. Quantitative data were analyzed using multilevel modeling, structural equation modeling, mediation and moderation analyses, and hierarchical regression, while qualitative evidence from executive interviews, focus group discussions, organizational documents, and case studies was examined through thematic analysis. Findings revealed that talent mobility exerted the strongest direct effect on organizational resilience, whereas organizational learning partially mediated this relationship by strengthening knowledge transfer, capability renewal, and adaptive performance. Leadership capability, learning agility, workforce flexibility, and employee engagement further enhanced resilience when supported by competency-based mobility systems and digital workforce platforms. Results indicate that organizational resilience emerges from strategically integrated human capital systems rather than isolated human resource practices. The proposed framework provides evidence-based guidance for organizational leaders seeking to align workforce capability, internal mobility, and organizational learning to strengthen long-term adaptability, innovation, and sustainable competitive advantage in dynamic business environments.